Resilience as a shield: protective and risk factors in a mediation model of cyberbullying among Thai secondary students - Junnoi, Wiranya; Damrongpanit, Suntonrapot (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study examined cyberbullying among 366 lower secondary studentsin Northern Thailand, confirming a four-component model (masquerade (MAS), exclusion (EXC), harassment (HAR), and outing (OUT)) with excellent empirical fit. Structural equation modeling revealed resilience as the strongest protective factor against cyberbullying behaviors (β=-0.282), while authoritarian parenting (AUT) emerged as a significant risk factor (β=0.195). AUT undermined self-esteem (β=-0.162) and social relationships (β=-0.267). Self-esteem proved to be a powerful resilience builder (β=0.578). Media influence showed a direct negative relationship with cyberbullying (β=-0.196) while diminishing resilience. Resilience functioned as a partial mediator between AUT and cyberbullying (variance accounted for (VAF)=0.201), demonstrating how harsh parenting indirectly increases cyberbullying risk by eroding psychological coping mechanisms. Resilience served as a complete mediator between self-esteem and cyberbullying (VAF=0.891), revealing that healthy self-perception primarily protects against cyberbullying by strengthening psychological resilience. Additionally, resilience operated as a competitive mediator in pathways involving social networks and media influence.